Cover Image, Volume 123, Number 1, January 2022. Issue 1 (27th January 2022) - Dufrusine, Beatrice; Damiani, Verena; Capone, Emily; Pieragostino, Damiana; Dainese, Enrico; De Marco, Margot; Reppucci, Francesca; Turco, Maria C.; Rosati, Alessandra; Marzullo, Liberato; Sala, Gianluca; Sallese, Michele; et al.
Abstract : Front Cover : The cover image is based on the Research Article BAG3 induces fibroblasts to release key cytokines involved in pancreatic cell migration by Beatrice Dufrusine et al., https://doi.org/10.1002/jcb.30172 .